Job Engagement, Organizational Citizenship Behavior, And Performance: The Moderating Role Of Job Satisfaction - Rizky Fitriani Rustam (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the determinants of employee performance by examining the influence of employee engagement and job satisfaction and evaluating the role of organizational citizenship behavior or OCB as an intervening variable and job satisfaction as a moderator. Using a quantitative approach with Structural Equation Modeling analysis techniques based on Partial Least Squares or SEM PLS, this study involved 120 Puskesmas employees in the Bombana Regency area as respondents selected through a structured survey technique. The results of statistical analysis provide empirical evidence that employee engagement has a positive and significant impact on performance and is the main predictor for the formation of OCB. In contrast, partial job satisfaction was shown to have no significant direct effect on performance, but important findings from the interaction test suggest that this variable functions effectively as a moderator in the relationship between OCB and performance. This indicates that job satisfaction will only have a real impact on improving work results if synergized with high organizational citizenship behavior. The conclusion of this study emphasizes that extra-role behavior or OCB is a vital key in the mechanism of improving health service performance which can be strengthened through the creation of employee job satisfaction.